2011
DOI: 10.1002/bab.32
|View full text |Cite
|
Sign up to set email alerts
|

Stable and high‐level production of recombinant Factor IX in human hepatic cell line

Abstract: Hemophilia B is a genetic disease of the coagulation system that affects one in 30,000 males worldwide. Recombinant human Factor IX (rhFIX) has been used for hemophilia B treatment, but the amount of active protein generated by these systems is inefficient, resulting in a high-cost production of rhFIX. In this study, we developed an alternative for rhFIX production. We used a retrovirus system to obtain two recombinant cell lines. We first tested rhFIX production in the human embryonic kidney 293 cells (293). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We were not only able to analyze the abundance and complexity of the proteome as it shifted during the bioprocess and after purification, but we were also able to monitor the abundance of diverse PTMs with site specificity, including the critically important g- Discussion rFIX is commercialized as a replacement therapy for Haemophilia B [8,10]. Considerable effort has been devoted to optimize rFIX bioprocess and expression systems [7,[10][11][12][109][110][111][112][113]. FIX is highly post-translationally modified with a variety of heterogeneous PTMs, and GLA domain gcarboxylation is the most functionally relevant PTM [14,[19][20][21].…”
Section: Predicting Purity Of Purified Rfix By Measuring Changes In Hmentioning
confidence: 99%
See 1 more Smart Citation
“…We were not only able to analyze the abundance and complexity of the proteome as it shifted during the bioprocess and after purification, but we were also able to monitor the abundance of diverse PTMs with site specificity, including the critically important g- Discussion rFIX is commercialized as a replacement therapy for Haemophilia B [8,10]. Considerable effort has been devoted to optimize rFIX bioprocess and expression systems [7,[10][11][12][109][110][111][112][113]. FIX is highly post-translationally modified with a variety of heterogeneous PTMs, and GLA domain gcarboxylation is the most functionally relevant PTM [14,[19][20][21].…”
Section: Predicting Purity Of Purified Rfix By Measuring Changes In Hmentioning
confidence: 99%
“…For example, rFIX N-linked glycans (native and engineered) influence rFIX in vivo half-life[94,[116][117][118][119] and may modulate rFIX activation[31], while rFIX EGF-like 1 Oglycans stabilize the domain and likely participate in protein-protein interactions[92,99]. Changes in the expression system and incubation conditions alter the number and variety of PTMs in recombinant proteins[7,10,11,21,70,109,114], and new, unexpected PTMs may appear. Indeed, through a detailed MS proteomic analysis we identified new PTMs on purified rFIX, including a sulfation/phosphorylation on Y45 , several Asp oxidations spread throughout the molecule, and new…”
mentioning
confidence: 99%
“…In mammals, the γ‐glutamylcarboxylation system has a very wide tissue distribution as it has been detected in nearly all cells and tissues isolated [25]. In line with this, academic and industrial laboratories have demonstrated successful expression of VKD protein in active form in several different mammalian cell lines such as AV12‐664, BHK, CHO, COS, HEK293, HepG2, huH‐7, SK‐Hep1 and rat hepatoma [10, 12, 13, 26–29]. Evolutionarily, the γ‐carboxylation system is of ancient origin, predating the mollusks [30].…”
Section: Vitamin K Dependent Clotting Factorsmentioning
confidence: 99%
“…30 mg/l [37]. It may be increased by 30-50% upon addition of 1 nM of methyl testosterone to the culture medium [38] or doubled after the addition of phorbol 12-myristate, 13-acetate, and calcium ionophore [39]. The appearance of undesired activated FIX in the culture medium can be controlled by decreasing the Ca 2+ ions concentration to 0.5 mM from 1.12 mM [40]; in another study of the same group, it was found that an increase of Ca 2+ ions to 1.3 mM leads to a 30% increase in the production of FIX, without a significant rise in the FIXa level [41].…”
Section: Improvements In Recombinant Fix Productionmentioning
confidence: 99%
“…Natural FIX is produced by liver cells, and it has been established that the human hepatoma cell line HepG2 produces 1.5 times more recombinant FIX than the human kidney cell line 293 after transfection by the same retroviral vector [39]. Nonvertebrate cultured cells were also evaluated for the expression of FIX, and in a drosophila-derived SF2 cell line a 12-fold increase in functionally active FIX secretion, compared with CHO cells, was detected [49].…”
Section: Improvements In Recombinant Fix Productionmentioning
confidence: 99%